Composite Outcome Improves Feasibility of Clinical Trials in Peritoneal Dialysis. Issue 5 (September 2019) - Boehm, Michael; Niewczas, Julia; Herkner, Harald; Koenig, Franz; Kratochwill, Klaus; Rutherford, Peter; Aufricht, Christoph; Vychytil, Andreas
Background: Peritoneal dialysis (PD) is complicated by a high rate of adverse events that might be attributed to cytotoxicity of currently used PD fluids. However, clinical development of novel PD fluids is virtually non-existent, in part due to difficulties in recruiting sufficiently large populations for adequately powered trials. The aim of this study is to understand the potential impact of introducing composite outcomes on clinical trial feasibility in PD. Methods: A composite outcome "major adverse peritoneal events (MAPE)" was designed to combine clinically relevant complications of PD, such as (1 ) technical failure (cause-specific for peritonitis and/or insufficient dialysis), (2 ) peritonitis, and (3 ) peritoneal membrane deterioration. Incidence rates of individual endpoints were obtained from the literature and expert panel estimations, and population sizes were computed based on Chi-square test for adequately powered confirmatory randomized controlled clinical trials with 2 parallel arms. Results: Incidence rates for technical failure, peritonitis, and peritoneal membrane deterioration were estimated at 15%, 50%, and 23%, respectively, at 2 years follow-up, with adequate agreement between the literature and expert opinion. Assuming that a given intervention reduces adverse outcomes by 30%, an adequately powered clinical trial needs to recruit up to 1, 720 patients when studying individual outcomes. Combining endpoints increases power in simulated trials despite considerable overlap, and the composite outcome MAPE reduces the required population to 202 patients aiming for 80% power. Conclusion: Introduction of the composite outcome MAPE, covering relevant major adverse peritoneal events, may improve the feasibility of clinical trials to adequately test novel PD fluids.